2010
DOI: 10.14430/arctic643
|View full text |Cite
|
Sign up to set email alerts
|

Forty-seven Years of Research on the Devon Island Ice Cap, Arctic Canada

Abstract: ABStRACt. The Devon Island ice cap has been the subject of scientific study for almost half a century, beginning with the first mass balance measurements in 1961. Research on the ice cap was the first to investigate (1) the role of meltwater in seasonal ice-velocity variations on a polythermal Arctic ice cap, (2) the use of air temperature rather than net radiation as a proxy for the energy driving surface melt, and (3) the influence of the changing frequency of specific synoptic weather configurations on glac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 62 publications
(87 reference statements)
4
34
0
Order By: Relevance
“…The formation and orientation of sastrugi and the associated surface roughness are dependent on the prevailing wind pattern over the glacier surface [e.g., Mather , ]. Because similar patterns of katabatic winds and sastrugi formation have been observed over multiple years on DIC [ Koerner , ; Boon et al ., ], we argue that despite the 10 year time span between data collection, a comparison with roughness data from 2004 is meaningful. The small‐scale surface roughness (10 cm point separation, 10 m baseline) ranges between 0.04 and 0.13 m and displays a general trend of increasing roughness with decreasing elevation (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…The formation and orientation of sastrugi and the associated surface roughness are dependent on the prevailing wind pattern over the glacier surface [e.g., Mather , ]. Because similar patterns of katabatic winds and sastrugi formation have been observed over multiple years on DIC [ Koerner , ; Boon et al ., ], we argue that despite the 10 year time span between data collection, a comparison with roughness data from 2004 is meaningful. The small‐scale surface roughness (10 cm point separation, 10 m baseline) ranges between 0.04 and 0.13 m and displays a general trend of increasing roughness with decreasing elevation (Figure b).…”
Section: Resultsmentioning
confidence: 99%
“…Without firn, these conditions were similar to those found during Baird's expedition in 1950 to the southern part of the ice cap (Baird et al, 1952) and to data reported by , where the snowpack completely melted during the spring. A shallow ice core drilling revealed the presence of superimposed ice (ice with a high density of air bubbles, see Boon et al, 2010;Zdanowicz et al, 2012). The snow surface altitude of the camp over 1 m of snow was 1084 AE 3 m (70.0113 N; À73.2712 W) derived from standard GPS measurements.…”
Section: In Situ Measurementsmentioning
confidence: 99%
“…Those datasets represent semi-continuous depth measurements. In our current method, we obtained ice cores using a 15 custom drill designed for Arctic sampling and conventional practices in ice sampling for temporal profiling (Boon et al, 2010;Readinger, 2006). Lastly, the Devon Ice Cap sampling locations in the earlier research were not at the summit of the ice cap as in the current research.…”
Section: Pfaa Concentrations and Fluxes On The Devon Ice Cap: Comparimentioning
confidence: 99%
“…Devon Ice Cap, located on the Devon Island in Nunavut, Canada, was previously sampled for PFAAs in May of both 2006 and 2008 through collection from the sidewall of a snow pit (MacInnis et al, 2017;Young et al, 2007). This ice cap has a high latitude and elevation (Boon et al, 2010) and is not expected to receive any local or oceanic sources of contamination. These previous studies detected PFAAs in snow profiles that spanned a 10 -14 year period in deposition.…”
Section: Introductionmentioning
confidence: 99%